Mediation effects of metabolites and sex hormones on the relationship between body mass index and breast cancer: Mendelian randomization analysis and mediation analysis - Yang, Yanjiang; Chen, Min; Yang, Wenwen (Frontiers in Oncology, 2024)
BackgroundObservational investigations have indicated a notable correlation between body mass index (BMI) and breast cancer (BC). Nevertheless, the precise biological pathways driving this correlation remain ambiguous. Consequently, we utilized Mendelian randomization (MR) techniques to explore the causative link between BMI and genetic predisposition to BC, as well as the potential intermediary influences.MethodsUtilizing extensive cohorts sourced from publicly accessible genome-wide association studies (GWAS) datasets of European populations, we conducted Mendelian randomization (MR) analysis. The primary method employed was the Inverse Variance Weighted (IVW) model. We evaluated both heterogeneity and horizontal pleiotropy. Our MR analysis unveiled several metabolites and sex hormones as mediators in the association between BMI and BC.ResultsThe IVW model indicated significant negative causal correlations between BMI and BC, ER+BC, and ER-BC. Thirty-five metabolites, thirty-three metabolites and sex hormones, and fifteen metabolites respectively mediated the causal effects of BMI on BC, ER+BC, and ER-BC. Furthermore, our study found that BMI influences BC risk through different mediating factors; BMI increases ER+BC risk through the pathway of sex hormones (biologically available testosterone) and decreases the causal relationship of BC risk through multiple metabolite pathways.ConclusionThis study discovered that BMI increases ER+BC risk through the pathway of sex hormones (biologically available testosterone), and decreases BC risk through multiple metabolite pathways causally. These discoveries could offer insights into the development of preventive strategies and interventions for BC, while further investigations should delve into alternative feasible biological pathways.